Durability Performance Of Lightweight Aggregate Concrete For Housing Construction - Zulkarnain, Fahrizal; Ramli, Mahyuddin (2008)

(untitled)
Durability can be defined as the ability of material to withstand the effects of its environment. In the building material its may be interpreted as chemical attack, water absorption and carbonation.